Individual-level socioeconomic status and cataract-induced visual disability among older adults in China: the overview and urban-rural difference - Fan, Yunyi; Guo, Shuai; Dai, Wanwei; Chen, Chen; Zhang, Chun; Zheng, Xiaoying (Frontiers in Public Health, 2024)
To investigate the prevalence of cataract-induced visual disability and its association with individual-level socioeconomic status (SES) among older adults in China.: Using the data of 354 743 older adults (60 years and older) from the Second China National Sample Survey on Disability in 2006. Cross-sectional study design was applied. The differences in visual disability prevalence of cataracts among sociodemographic subgroups were analyzed by the chi-square test, and the association between individual-level SES and cataractinduced visual disability was investigated by the multivariate logistic regression model.Results: The weighted visual disability prevalence of cataracts was 4.84% in 2006. Older people with a higher household income per capita (OR=0.83, 95% CI: 0.81-0.85), higher education level (primary school vs. illiteracy: OR=0.80, 95% CI: 0.76-0.83; ≥undergraduate college vs. illiteracy: OR=0.31, 95% CI: 0.25-0.39), and occupation (OR=0.53, 95% CI: 0.50-0.56) were less likely to suffer from cataract-induced visual disability. Household income per capita and education level increase played a greater role in decreasing the risk of visual disability caused by cataracts in urban areas, while having occupation contributed more to reducing the risk of disability in rural areas.The gap in individual-level SES is closely related to the visual health inequities among older Chinese people and there are two distinct mechanisms in rural and urban areas. Strategies to promote collaborative healthcare development regionally, strengthen safeguards for disadvantaged groups, and increase public awareness of visual disability prevention are warranted.